An introduction to philosophy of education - Barrow, Robin; Woods, R. G. (Ronald George) (New York, NY : Routledge, 2021)
'This introductory text, now in its fifth edition, is a classic in its field. It shows, first and foremost, the importance of philosophy in educational debate and as a background to any practical activity such as teaching. In addition to these questions, which strike to the heart of the rationale for the educative process as a whole, the author explores such concepts as culture, creativity, autonomy, indoctrination, needs, interests, and learning by discovery. Updates to this edition include new chapters on religious education and moral education, as well as questions for reflection at the end of each chapter'--
Includes bibliographical references and index.
Keywords: Education -- Philosophy